A cascade of exclusion: administrative burdens and access to citizenship in the case of Argentina's National Identity Document. (December 2022) - Chudnovsky, Mariana; Peeters, Rik
Administrative burdens can hinder people's social, political and economic participation. However, most empirical studies usually tackle the issue of how they affect access to citizenship merely indirectly. This article examines administrative exclusion from Argentina's National Identity Document and its effects on a key social policy: the Universal Child Allowance. Findings indicate that: (1) administrative exclusion from official identity documents 'feeds back' into the construction of a vulnerable target group that is systematically excluded from social benefits and public services; and (2) limitations in the administrative capacity for identity registration and documentation 'trickle down' to complications in the implementation of social policies as target groups remain 'off the radar'. Findings also demonstrate the importance of understanding administrative burdens as a systemic issue. Burdens manifest themselves at the level of citizen–state interactions but their causes and consequences are tied up with intractable institutional characteristics, administrative capacities and social inequalities. Points for practitioners: Efforts by developing countries to develop effective social protection systems are often thwarted by limitations in the state's capacity to identify and reach marginalized citizens. This suggests the need for a systemic perspective of the state's entire capacity instead of merely focusing on the design of social protection programmes. Specifically, we demonstrate that complete, accessible and up-to-date civil registries, identity documents and other forms of registration are a precondition for transforming formal rights into a tangible reality for citizens.